2014
DOI: 10.3928/01477447-20141124-07
|View full text |Cite
|
Sign up to set email alerts
|

No Decreased Infection Rate When Using Antibiotic-Impregnated Cement in Primary Total Joint Arthroplasty

Abstract: There has been much debate and controversy about the routine use of antibiotic-impregnated bone cement in primary total joint arthroplasty. The purpose of this study was to undertake a meta-analysis to determine whether the use of antibiotic-impregnated bone cement would reduce the incidence of infection after primary total joint arthroplasty. Of 313 citations identified for screening, 6 trials reporting 26,791 patients were eligible for data extraction and meta-analysis. The authors found no statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…TKA: Two meta-analyses [68, 69] concluded that the use of ALBC does not decrease the rate of deep or superficial infections compared to plain bone cement. One meta-analysis [70], including both TKA and THA surgeries, found a significantly lower risk of deep infections and no effect on the risk of superficial infections when ALBC was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TKA: Two meta-analyses [68, 69] concluded that the use of ALBC does not decrease the rate of deep or superficial infections compared to plain bone cement. One meta-analysis [70], including both TKA and THA surgeries, found a significantly lower risk of deep infections and no effect on the risk of superficial infections when ALBC was used.…”
Section: Resultsmentioning
confidence: 99%
“…THA: One meta-analysis concluded that ALBC did not lower the rate of deep or superficial infection rate [69]. As described above, another meta-analysis concluded ALBC reduced the rate of deep infection in THA, but not TKA surgeries [70].…”
Section: Resultsmentioning
confidence: 99%
“…ALBC has been in use since first being developed in 1970 as a potential method for in situ drug release [59] . Despite its widespread use, the antimicrobial efficacy of ALBC is debated [60,61] . Due to irregular release of antibiotic, only 5%-8% of the drug typically elutes properly [62] .…”
Section: Antibiotic-loaded Bone Cementmentioning
confidence: 99%
“…And from this point of view, lower overall infection rate might make it hard to reach statistical significance in the present study even though 1,138 cases had been recruited. Similarly, other reports which could not find significant difference with or without ALBC showed lower occurrence rate of deep infection, specifically, lower than 1.5% in the report by McQueen, et al [11], Hinarejos, et al [12], and Zeng, et al [20].…”
Section: Discussionmentioning
confidence: 61%